Wound Healing Property and Phytochemical Analysis of Zanthoxylum Species from Uganda - Ogwang, Patrick Engeu; Ronald, Angupale Jimmy; Joseph, Oloro; Evariste, Baruga (My University, 2017)
Aim: The study evaluated the efficacy and possible mechanism of the stem bark of Zanthoxylum species used by communities and herbalists for wound healing in South Western Uganda. Study Design: Experimental controlled. Place and Duration: Departments of Pharmacy, Pharmacology and Pharmaceutical Sciences, Faculty of Medicine, Mbarara University of Science and Technology. The study done between August 2016 and February 2017. Methodology: Excision wounds were humanely made on the bark of healthy albino rats and then randomly divided into four groups i.e Group I (Zanthoxylum spp (Zanthoxylum species) water extract) n=9, Group 2 (control herbal drug) n=6, Group 3 (distilled water) n=9 and Group 4 (neomcycine antibiotic) n=3. Treatments were applied twice a day for 15 days. The wound areas determined at baseline (day 1), then at day 6 and day 15 for each of the animals in groups 1, 2 and 3. Percentage reduction in wound areas was determined on day 6 and 15 and statistically compared. On day 7 the rats in group 4 and three rats randomly picked by a blinded laboratory technician from groups 1 and 3 were humanely sacrificed for histology examination of wound tissues. Phytochemical analysis of the water extract of Zanthoxylum spp and the effect of the various solvent on extract efficacy were also evaluated. Results: The Plant Zanthoxylum spp water extract was found to significantly reduce wound areas better than distilled water on day 6 and 15, (55.93±2.845) Vs (35.06±3.508), p=0.0312 and (93.18±1.721) Vs (74.89±5.604), p=0.0097, and marginally better than herbal control drug on day 6, ( 55.93±2.845) Vs (39.55 ± 6.524), p=0.0799. Five previously known alkaloids were identified by HPLC and LC-MS methods in the plant species as possible active compounds in wound healing. No significant difference was observed in the effects of the solvents on the efficacy of Zanthoxylum species on wound healing. Conclusion: Zanthoxylum species studied shows great potential for stimulation of collagen formation and promoting natural wound healing mechanisms and therefore offers an alternative for wound treatment.
Keywords: Zanthoxylum species; wound; healing; alternative